2018
DOI: 10.1111/head.13362
|View full text |Cite
|
Sign up to set email alerts
|

Headache Characteristics in Children With Pseudotumor Cerebri Syndrome, Elevated Opening Pressure Without Papilledema, and Normal Opening Pressure: A Retrospective Cohort Study

Abstract: While missing data and small cohort size are limitations, this study suggests that headache in PTCS is more likely to involve the head along with neck/shoulders, and that headache in PTCS may be episodic or constant. Headache is occasionally absent in PTCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
2
14
1
Order By: Relevance
“…Headache is the most common presenting symptom of PTCS, found in up to 98% of children with primary and secondary PTCS, 1,51,52 presenting more often in older children. It is found in nearly all PTCS without papilledema, given that headache is the primary symptom in this rare diagnosis.…”
Section: Headache Versus Migraine Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Headache is the most common presenting symptom of PTCS, found in up to 98% of children with primary and secondary PTCS, 1,51,52 presenting more often in older children. It is found in nearly all PTCS without papilledema, given that headache is the primary symptom in this rare diagnosis.…”
Section: Headache Versus Migraine Symptomsmentioning
confidence: 99%
“…53 Headache features in children with PTCS had not been studied until recently. Hamedani et al 52 found that episodic and chronic headaches in children were equally present, and the majority of the headaches were rated as severe. The pain was more often localized to the head and neck or shoulders.…”
Section: Headache Versus Migraine Symptomsmentioning
confidence: 99%
“…In contrast, the characteristics of headache in pediatric PTCS are more widely variable. Headache in PTCS may be daily or constant but also may be entirely episodic, and the pain may be diffuse or focal [23,24]. Headache in pediatric PTCS is more likely to involve the neck and shoulders, perhaps related to sensitivity towards distention of the spinal root dural sheaths with increased pressure [23].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Headache in PTCS may be daily or constant but also may be entirely episodic, and the pain may be diffuse or focal [23,24]. Headache in pediatric PTCS is more likely to involve the neck and shoulders, perhaps related to sensitivity towards distention of the spinal root dural sheaths with increased pressure [23]. Importantly, the "classic" high-pressure headache triad of (i) daily headache; (ii) worsening with Valsalva; and (iii) diffuse nonpulsating pain was found to be present in only 36.6 % of children with PTCS [23,26].…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation